Pengaruh Kualitas Pelayanan Dan Fasilitas Wisata Terhadap Kepuasan Pengunjung Saat Penerapan New Normal ( Studi Kasus Pada Pengunjung Tempat Wisata Selo Tirto Giri (Setigi) Gresik ) - Luklu’ul Lum’ah; Agus Widarko; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractIndonesia is a country that has many advantages to increase economic growth, one of which is the tourism sector. The tourism sector is an industry that is growing rapidly in the middle of the times and has becomes of the largest and strongest industries in the world. This is because the industrial revolution 4.0 is the development of the internet which has an impact on easy access to information. This convenience creates a new lifestyle for people in seeking satisfaction in the tourism and culinary sectors. Where people will easily find the destination point tourism only with gedget and internet. Indonesia is an archipelago with different natural conditions and has the potential to become a tourist spot. One of them in Gresik Regency is the Selo Tirto Giri (SETIGI) tourist spot. Many local tourists and foreign tourists who come to visit to enjoy and seek inner satisfaction in SETIGI nature tourism. Tourist satisfaction is not only in the beauty of the tourist attractions, but is supported by the services and facilities available at these tourist attractions. This study examines the quality of service and facilities for tourist attractions on visitor satisfaction. The method used in this research is descriptive quantitative, where data is obtained through distributing questionnaires to tourists and then processed with SPSS and analyzed by researchers. The results of the study indicate that service quality and tourist facilities simultaneously and partially have a significant effect on visitor satisfaction during the implementation of the  new normal (study on visitors to the Selo Tirto Giri (SETIGI) tourist spot, Sekapuk Village, Ujungpangkah district, Gresik).  Keywords: quality of servants, tourist facilities, visitor satisfaction